2013
DOI: 10.1371/journal.pone.0083228
|View full text |Cite
|
Sign up to set email alerts
|

B-lymphocytes as Key Players in Chemical-Induced Asthma

Abstract: T-lymphocytes and B-lymphocytes are key players in allergic asthma, with B-lymphocytes producing antigen-specific immunoglobulins E (IgE). We used a mouse model of chemical-induced asthma and transferred B-lymphocytes from sensitized animals into naïve wild type mice, B-lymphocyte knock-out (B-KO) mice or severe combined immunodeficiency (SCID) mice. On days 1 and 8, BALB/c mice were dermally sensitized with 0.3% toluene diisocyanate (TDI) (20µl/ear). On day 15, mice were euthanized and the auricular lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…the mouse chitinase YM-1 (Wisnewski et al, 2015). It has also been suggested that B1-lymphocytes, transferred from dermally TDI-sensitized mice, contribute to an innate-like rapid defense upon a TDI challenge in recipient mice (De Vooght et al, 2013). How these previous studies are related to our study remains to be shown.…”
Section: Discussionmentioning
confidence: 65%
“…the mouse chitinase YM-1 (Wisnewski et al, 2015). It has also been suggested that B1-lymphocytes, transferred from dermally TDI-sensitized mice, contribute to an innate-like rapid defense upon a TDI challenge in recipient mice (De Vooght et al, 2013). How these previous studies are related to our study remains to be shown.…”
Section: Discussionmentioning
confidence: 65%
“…Based on previous evidence [49], a role for allergen cross-linking with IgEs seems unlikely. However, there is no doubt that the adaptive immune system is also involved, both because the induction of AHR relies on an antigen-specific challenge and because our model is dependent on properly functioning lymphocytes, as shown here with Rag2 knockout mice and previously in severe combined immunodeficiency disease mice [11] and in adoptive lymphocyte transfer experiments [33,34].…”
Section: Discussionmentioning
confidence: 70%
“…Taken together, the above results allowed us to conclude, first, that TRPA and TRPV1 are necessary, but not sufficient, to induce AHR in TDI-sensitised animals and, second, that a specific adaptive immune response is involved and necessary to induce AHR in such TDI-sensitised animals. Previous research on our mouse model has shown that lymphocytes are crucially involved in the development of TDI-induced asthma in Balb/c mice [33,34]. To determine whether this is also the case in the current model of chemical-induced AHR, using C57Bl/6 mice, we used Rag2 knockout mice, lacking mature lymphocytes.…”
Section: Involvement Of Immune Cells In Tdi-induced Ahrmentioning
confidence: 99%
“…The observation that diisocyanates induce skin contact hypersensitivity, and that skin exposure to TDI is employed in experimental models to induce sensitization [32] , is of interest for us. In unpublished work we note that many genes/proteins downstream of ATX signaling are the same as those induced by test substances in cell-based tests for skin sensitizers [33] .…”
Section: Cell Based Test Models For Skin and Respiratory Sensitizersmentioning
confidence: 99%